Remission of ALK-negative primary pulmonary inflammatory myofibroblastic tumor on treatment with clarithromycin: A case report and review of the literature - WATANABE, HIDEHIRO (Oncol Lett, 2016)
Inflammatory myofibroblastic tumors (IMTs) belong to an intermediate group of soft-tissue tumors, they are relatively rare but exhibit a wide range of pathologies, from benign to malignant. At present, no standard treatment has been established, however, it is known to be important to determine the grade of malignancy of the tumor, prior to treatment. The present study reports a 73-year-old female patient with no clinical manifestations, who, when examined radiographically at a health check exhibited bilateral thoracic infiltrative shadows and nodular shadows by chest CT. A metastatic tumor or an organizing pneumonia were suspected. Blood examination showed no abnormal findings, and a pathological diagnosis of IMT was given from the histological findings of the tissue extracted by video-assisted thoracic surgery. Histological analysis established the lack of expression of anaplastic lymphoma kinase (ALK1) and immunoglobulin subtype G4 (IgG4). Alteration of the radiological shadows was observed over several weeks, and after concluding that chronic inflammation was worsening the patient's condition, clarithromycin was administered as a long-term macrolide therapy. The IMT decreased in size, and eight months later it had almost resolved. The patient was last reported to be maintaining a stable condition with no relapse. Some IMT cases have malignant pathology, and should be carefully followed-up. However, in the present case, where the IMT is both ALK1-negative and IgG4-negative, its biological immune responsiveness appears to differ from positive cases, and an inflammatory response was predominant. Clarithromycin, has immunomodulatory and anti-inflammatory effects and appeared to be effective in treating the IMT of the patient in the present study.